2012
DOI: 10.1039/c2cc35034c
|View full text |Cite
|
Sign up to set email alerts
|

New tetramethylthiepinium (TMTI) for copper-free click chemistry

Abstract: A new derivative of the strained 3,3,6,6-tetramethylthiacycloheptyne (TMTH) bearing a functional handle is reported. Following an optimized synthesis, the handle was introduced by mild alkylation of the sulphur atom. The resulting functionalized strained 4,5-didehydro-3,3,6,6-tetramethyl-2,3,6,7-tetrahydrothiepinium (TMTI) proved to be stable and underwent extremely fast [3+2] cycloaddition reaction with benzyl azide in both organic and aqueous solvents. The reaction was equally efficient in cell lysate and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Attempts in this direction by Wagner et al underlined this requirement. 18 Thus we set out to develop a practical synthesis of a new and stable TMTH click reagent, in which unwanted side reactions can be mitigated by optimal reaction conditions and which above all contains a functional group for convenient introduction of a variety of linkers for ligand attachment.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts in this direction by Wagner et al underlined this requirement. 18 Thus we set out to develop a practical synthesis of a new and stable TMTH click reagent, in which unwanted side reactions can be mitigated by optimal reaction conditions and which above all contains a functional group for convenient introduction of a variety of linkers for ligand attachment.…”
Section: Introductionmentioning
confidence: 99%
“…This rate is on par with many commonly used distortion-accelerated azide-alkyne cycloadditions. 2,[44][45][46][47] Under similar conditions, no reactivity was observed between 6substituted triazine (1) and TMTH (9) (Fig. S12 †).…”
mentioning
confidence: 92%
“…But this process gave a mixture of 1,4‐ and 1,5‐disubstituted 1,2,3‐triazole isomers. Meldal et al and King et al found that copper(Ι) catalyzes azide–alkyne cycloaddition (CuAAC) and only one regioisomer (1,4‐disubstituted 1,2,3‐triazole) can be obtained using this procedure. Also they concluded that copper(Ι) can increase the reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…Also they concluded that copper(Ι) can increase the reaction rate. There are some other methods for producing these compounds including copper‐free cycloaddition (CFC) strategies, but their regioselectivity and/or rate of the reaction is low. In some cases, CFCs need organic solvents and longer reaction times .…”
Section: Introductionmentioning
confidence: 99%